Does body mass index impact the outcomes of tubeless percutaneous nephrolithotomy?. (20th February 2014) - Kuntz, Nicholas J.; Neisius, Andreas; Astroza, Gastón M.; Tsivian, Matvey; Iqbal, Muhammad W.; Youssef, Ramy; Ferrandino, Michael N.; Preminger, Glenn M.; Lipkin, Michael E.
<x xml:space="preserve">Abstract</x> Objective To evaluate whether body mass index (BMI) has an impact on the outcomes of tubeless percutaneous nephrolithotomy (PCNL). Patients and Methods We retrospectively reviewed patients who underwent tubeless PCNL at our institution from 2006 to 2011. Specifically, stone‐free rates, complications, and hospital length of stay (LOS) were assessed. Patients were divided into four groups based on BMI: <25, 25–29.9, 30–34.9 and ≥35 kg/m2. Baseline characteristics and outcomes were compared between BMI groups. Multivariable logistic regressions were used to evaluate the independent contribution of BMI as a predictor of outcomes. Results We identified 268 patients who fulfilled study requirements. The overall stone‐free and complication rates were 52.5% and 19.0%, respectively. Minor and severe complication comprised 10.4% and 8.6%, respectively. Univariate and multivariable analyses showed no association between BMI and stone‐free or complication rates. However, patients with a normal BMI had significantly higher transfusion rates (P = 0.005), and were significantly more likely to have a prolonged LOS (≥2 days), when compared with an overweight BMI (P = 0.032) Conclusions BMI did not impact the stone‐free, or complication rates of tubeless PCNL. Normal BMI was found to be a risk factor for prolonged LOS, which may be due to an increase in clinically significant bleeding in this patient population. Tubeless PCNL appears to be a safe and effective procedure for the treatment of complex renal calculi, independent of BMI.